Frequency of Metabolic Syndrome in Male Patients with Rheumatoid Arthritis: A Cross-Sectional Study - Sarah Sadr; Saeed Dashti dargahloo; Fatemeh Niksolat; Aref Hoseinian; Maryam Mobini; Maryam Karimi (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: Rheumatoid arthritis (RA) is an autoimmune disease that increase the risk of coronary artery diseases. Metabolic syndrome (MetS) is considered as a risk factor for developing coronary artery diseases. There are some concerns about the association between RA and MetS, therefore, this study was done to evaluate the prevalence of MetS in male RA patients. Materials and methods: In a cross sectional study, male RA patients (n= 50) were evaluated regarding demographic and clinical features including disease activity score 28 (DAS28), health assessment questionnaire (HAQ), visual analogue scale (VAS), and laboratory parameters and compared with 50 age-matched controls. MetS was diagnosed according to the 2005 National Cholesterol Education Program Adult Treatment Panel III (NCEP/ATP III) and International Diabetes Federation (IDF) definition. The prevalence of MetS was compared in RA patients and controls. Statistical analysis was performed in SPSS V19, and results were considered significant at P< 0.05. Results: The mean ages of RA patients and controls were 49.04±10.2 and 46.12± 9.4 years, respectively (P= 0.139). MetS according to NCEP and IDF criteria was present in 12 (24%) and 18 (36%) of RA patients vs 16 (32%) and 18 (36%) of controls, respectively that was not significantly different. Controls were more likely to have hyperglycemia and hypercholesterolemia, especially higher levels of low density lipoprotein (P<0.05). Conclusion: According to the present study, prevalence of MetS was similar in RA patients and controls. MetS components should be routinely investigated in male RA patients to reduce the occurrence of MetS and its complications.